Ingesting a sports drink enhances simulated ice hockey performance while reducing perceived effort - Palmer, M. S.; Heigenhauser, G.; Duong, M.; Spriet, L. L. (International Journal of Sports Medicine, 2017)
This study determined whether ingesting a carbohydrate-electrolyte solution (CES) vs. progressive dehydration affected skeletal muscle glycogen use and performance in ice hockey players during simulated ice hockey exercise comprised of 3 active "periods". Seven males (21.3±0.3 years, 184.7±1.2?cm, 84.2±3.9 kg, and 49.6±1.8 mL·kg-1·min-1) performed a hockey-specific protocol on two occasions and either dehydrated progressively (NF), or stayed well-hydrated by ingesting a CES. Muscle biopsies were taken at rest, before the 3rd period (P3), and after the final sprint in the protocol. Compared to dehydration in the NF trial (-1.8% BM), CES ingestion enhanced voluntary performance (151.0±8.0 vs. 144.1±8.7 kJ) and glycogen use (177.5±31.1 vs. 103.5±16.2 mmol·kg dm-1), and reduced perceived exertion (16±1 vs. 18±1) in P3. Mean core temperature was reduced by CES ingestion throughout the protocol (38.0±0.2 vs. 38.1±0.1°C). These results suggest that compared to progressive dehydration, staying hydrated by ingesting a CES helps preserve performance, while reducing thermal and perceptual strains, in P3 of cycle-based simulation of ice hockey exercise. These benefits are observed despite greater glycogen use in P3 with CES ingestion.